Policy options for mitigating impacts of COVID-19 on domestic rice value chains and food security in West Africa - Arouna, Aminou; Soullier, Guillaume; Mendez del Villar, Patricio; Demont, Matty (Elsevier, 2020)
Rice plays a strategic role in food security in West Africa. However, the region increasingly relies on rice imports due to a growing and structural deficit, and domestic value chains face constraints in technology, finance and coordination. As a result, West Africa is very vulnerable to international and local trade disruptions, such as the ones currently inflicted by the COVID-19 pandemic. We build on evidence of the current state of domestic rice value chain upgrading in West Africa to anticipate the impacts of the COVID-19 pandemic on rice value chains’ resilience and their capacity to sustain food security in the region. Several policy options are proposed to help West African governments mitigate the impacts of the COVID-19 crisis on food security.